Probabilistic Design - The Future of Rock Engineering - Nielen Merwe (International Journal of Mining and Geo-Engineering, 2012)
A brief background to the development of the rock engineering design process is given, showing that since the development of the science of mathematics, deterministic methods have been used to perform various calculations. The variability of rock properties and support characteristics have always been known. However, they were not explicitly used in design but compensated for by the use of a safety factor, i.e. making a design more stringent than required by the calculations. The problem with this procedure is that the effect of increasing a safety factor on the overall stability of the design cannot be known because the range of variability is not incorporated in the design. The only way to overcome this problem is to make use of the science of probability. In doing that, the ranges of rock qualities are explicitly included in the design and the probability of failure is exposed. Examples of common rock engineering calculations in mining are provided, showing that the probabilistic designs are not difficult or time consuming to perform and yield much more useful outcomes than merely using a safety factor.